Phylogeographical structure of the pygmy shrew: revisiting the roles of southern and northern refugia in Europe. (13th February 2020) - Vega, Rodrigo; McDevitt, Allan D; Stojak, Joanna; Mishta, Alina; Wójcik, Jan M; Kryštufek, Boris; Searle, Jeremy B
Abstract: Southern and northern glacial refugia are considered paradigms that explain the complex phylogeographical patterns and processes of European biota. Here, we provide a revisited statistical phylogeographical analysis of the pygmy shrew Sorex minutus Linnaeus, 1766 (Eulipotyphla, Soricidae), examining its genetic diversity, genetic differentiation and demographic history in the Mediterranean peninsulas and in Western and Central Europe. The results showed support for genetically distinct and diverse phylogeographical groups consistent with southern and northern glacial refugia, as expected from previous studies. We also identified geographical barriers concordant with glaciated mountain ranges during the Last Glacial Maximum (LGM), early diversification events dated between the Late Pleistocene and Early Holocene for the main phylogeographical groups, and recent (post-LGM) patterns of demographic expansions. This study is the most comprehensive investigation of this species to date, and the results have implications for the conservation of intraspecific diversity and the preservation of the evolutionary potential of S. minutus .